Physical Caregiving and Stress- An examination of Mediating Role of Social Support to Caregivers of Pediatric Cancer Patients in Pakistan - Qurat-ul-ain, Ansa; Marzuki, Najib Ahmad (Advances in Social Sciences Research Journal, 2017)
Informal caregivers has always been a significant source of providing care to the individuals with chronic illness such as cancer. Diagnosis of cancer in children can have harmful effects on a psychosocial and emotional well-being of a caregiver. Considering the caregiver stress theory as a theoretical framework, the purpose of this research was to determine the relationship of physical caregiving to the children with cancer in relation to caregivers’ stress taking social support as a mediator. The data was collected from 100 primary caregivers of children aged 0-19 years from hospitals of Pakistan using measurement scales of Caregiving task questionnaire, Medical Outcomes Study-Social Support Survey and Modified Caregiver Strain Index. For data analysis, descriptive statistics and multivariate analysis were conducted. Findings showed positive correlation of physical caregiving and social support with caregivers’ stress as well as significant mediating effects of social support on caregivers’ stress. This suggests that social support is a resource of mental health for caregivers of children with cancer highlighting the importance of social support while designing and implementing caregiver health interventions.